Bidding in common value fair division games: The winner's curse or even worse? - Alice Becker; Tobias Brünner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
A unique indivisible commodity with an unknown common value is owned by group of individuals and should be allocated to one of them while compensating the others monetarily. We study the so-called fair division game (Güth, Ivanova-Stenzel, Königstein, and Strobel (2002, 2005)) theoretically and experimentally for the common value case and compare our results to the corresponding common value auction. Whereas symmetric risk neutral Nash equilibria are rather similar for both games, behavior differs strikingly. Implementing auctions and fair division games in the lab in a repeated setting under first- and second-price rule, we find that overall behavior is much more dispersed for the fair division games than for the auctions. Winners' profit margins and shading rates are on average slightly lower for the fair division game. Moreover, we find that behavior in the fair division game separates into extreme overand underbidding.
Keywords: C73; C91; D44; 330; common value auction; winner's curse; fair division game; Auktionstheorie; Spieltheorie; Gerechtigkeit; Test